Effect of Whole Protein Spore Myxobolus koi by Oral Treatment on Non-Specific Immune Response of Punten Carp (Cyprinus carpio L.) Infested with Myxobolus koi - Wiwin Sumiati; Gunanti Mahasri; Sri Subekti (Journal of Aquaculture and Fish Health, 2023)
Increased intensive cultivation of Punten Carp (Cyprinus carpio L.) is quite profitable, but on the other hand, it can result in a decrease in water quality due to uncontrolled leftover feed. Poor water quality can cause fish to become stressed then susceptible to disease, one of which is Myxobolus koi parasite infestation. The purpose of this study was to determine the effect of immunostimulant treatment of whole protein Myxobolus koi spores on the blood profile of Myxobolus-infested punten carp. The method used was an experiment with two treatments, the treatment without Myxobolus koi spore whole protein (P0) and the treatment of commercial feed added with an immunostimulant from Myxobolus koi spore whole protein of 5 µg/kg feed (P1). The study was conducted for 28 days and observed on days 0, 7, 14, 21, and 28, including the calculation of the number of erythrocytes, leukocytes, leukocyte differential, and water quality as supporting data. The abundance of erythrocytes in fish treated with P1 (1.16x106 cells/mm3-2.44x106 cells/mm3) was higher than in fish treated with P0 (1.09x106 cells/mm3-1.55x106 cells/mm3). The abundance of leukocytes in fish treated with P1 (3.79x104 cells/mm3-11.31x104 cells/mm3) was higher than in fish treated with P0 (3.51x104 cells/mm3-6.58x104 cells/mm3). The results of differential observations of leukocytes in the P0 treatment found basophils (0.3-1.3%), neutrophils (12.3-21.5%), eosinophils (2.5-4.9%), lymphocytes (61.9-76.8%) and monocytes (3.8-6.3%). The results of differential observations of leukocytes in the P1 treatment found basophils (0.3-1.0%), neutrophils (10.7-19.9%), eosinophils (2.4-3.9%), lymphocytes (61.8-72.6%) and monocytes (3.9-5.4%).